Qualitative interviews in cognitive disorders caused by dementia: Addressing methodological, ethical challenges (Part II) - Fatemeh Bahramnezhad; Mahdi Shafiee Sabet; Nahid Dehghan Nayeri (حیات)
As explained in the first part, the acquisition of firsthand experiences is an essential element of qualitative research for uncovering and enriching study findings. However, individuals with cognitive disorders are often excluded due to various challenges. In these cases, researchers may rely on caregivers or close associates to understand their feelings and views. This approach not only reduces these individuals to mere objects but also presents ethical dilemmas, thereby impacting the depth and richness of study findings (1). Given that the methods of data collection significantly impacts the results of studies (2), it is imperative for qualitative researchers to strive towards directly gathering information from the individuals themselves. Understanding the experiences of people with cognitive impairments is crucial for providing evidence-based services. However, these patients often encounter challenges such as speech difficulties (3), ‘pseudo-reminiscences’ (4-6), mood fluctuations and behavioral problems (7), and other issues. Therefore, researchers should take into consideration certain factors when conducting interviews with these individuals as in-depth interviews aim to gain a deeper understanding of participants' life experiences (8,9). These interviews require specialized skills across various stages, encompassing the development of interview guides, participant recruitment, obtaining consent, conducting effective interviews, data analysis and interpretation, and proficient communication and dissemination of research findings. This section delves into the key aspects of each of these phases. During interviews, it is important to prioritize the well-being of both the researcher and the participant while reflecting on and ensuring the depth and richness of the interview content (6).